2017
DOI: 10.1111/coa.13005
|View full text |Cite
|
Sign up to set email alerts
|

Eight weeks of omeprazole 20 mg significantly reduces both laryngopharyngeal reflux and comorbid chronic rhinosinusitis signs and symptoms: Randomised, double‐blind, placebo‐controlled trial

Abstract: The results of our trial suggest that omeprazole 20 mg OD for 8 weeks was effective in reducing signs and symptoms of both LPR and CRS, although in most patients still present at the end of the trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 31 publications
(87 reference statements)
1
53
0
Order By: Relevance
“…Proton pump inhibitors play a key role in management of suspected reflux‐associated CRS. Vaezi et al, in a DBRCT demonstrated a reduction in PND, SNOT‐20, and Quality of Life in Reflux and Dyspepsia scores in PND patients treated with lansoprazole 30 mg twice daily for 16 weeks vs placebo 679 . Median symptoms score improvement for patients treated with a PPI at 8 and 16 weeks was 55 and 50 respectively, relative to 3.5 and 5.0 for controls.…”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 96%
See 2 more Smart Citations
“…Proton pump inhibitors play a key role in management of suspected reflux‐associated CRS. Vaezi et al, in a DBRCT demonstrated a reduction in PND, SNOT‐20, and Quality of Life in Reflux and Dyspepsia scores in PND patients treated with lansoprazole 30 mg twice daily for 16 weeks vs placebo 679 . Median symptoms score improvement for patients treated with a PPI at 8 and 16 weeks was 55 and 50 respectively, relative to 3.5 and 5.0 for controls.…”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 96%
“…Anzic et al performed a DBRCT where patients with diagnosed LPR and comorbid CRS received 8 weeks of omeprazole 20 mg twice daily. They found objective reductions in reflux symptom index and scores, improved symptoms of comorbid CRSsNP, and improved endoscopy scores 679 …”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 97%
See 1 more Smart Citation
“…This may have led to overuse of proton pump inhibitors and increased medical cost. Although studies have shown that treatment of LPR symptoms also decreased nasal symptoms in chronic rhinosinusitis 19 and decreased nasal resistance on rhinomanometry, 20 proton pump inhibitors should not be initiated in all non-allergic rhinitis patients with a high reflux symptom index. Clinicians should treat moderate to severe nasal symptoms first.…”
Section: Discussionmentioning
confidence: 99%
“…It does seems that GERD could worsen the symptoms of bronchiectasis and a Korean group suggested that treatment with proton-pump inhibitors in bronchiectasis patients with a high body mass index could improve lung function [29]. However, the same association between GERD and worse respiratory symptoms can be found for asthma, CRS and COPD [30,31]. Although the association between GERD and all these chronic airway diseases is clear, a causal connection has not yet been established and further investigation considering potential confounding factors is surely needed.…”
Section: Introductionmentioning
confidence: 99%